Essential University Physics: Volume 1 (4th Edition) Clone

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 8 - Exercises and Problems - Page 148: 66

Answer

The proof is below.

Work Step by Step

We know equation 8.5: $U=GMm(\frac{1}{r_1}-\frac{1}{r_2})$ We must show that $U=mg\Delta r$, so we find: $GMm(\frac{1}{r_1}-\frac{1}{r_2})=mg\Delta r$ $GM(\frac{1}{r_1}-\frac{1}{r_2})=g\Delta r$ We know from the book the $\Delta r = r_1-r_2$, so we find: $GM(\frac{1}{r_1}-\frac{1}{r_2})=g( r_1-r_2)$ $g( r_1-r_2)=g( r_1-r_2)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.